2023
DOI: 10.3390/ijms24065252
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Pathway Is Involved in Chemoresistance and Cell Cycle Arrest Induction in Colon Cancer Cell Line Spheroids

Abstract: The presence of cancer stem cells (CSCs) has been associated with the induction of drug resistance and disease recurrence after therapy. 5-Fluorouracil (5FU) is widely used as the first-line treatment of colorectal cancer (CRC). However, its effectiveness may be limited by the induction of drug resistance in tumor cells. The Wnt pathway plays a key role in the development and CRC progression, but it is not clearly established how it is involved in CSCs resistance to treatment. This work aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Given that in this study we found that mut-p53 activates β-catenin/Wnt signaling, and we have recently reported that canonical Wnt activation plays an essential role in inducing chemoresistance to 5-FU in colon cancer cells (Moreno-Londoño et al. 2023 ), we investigated whether mut-p53 could participate in the induction of chemoresistance to 5-FU. We found that endogenous expression of wtp53 explains the sensitivity to low doses in the RKO cell line, contrary to mutp53, where more concentration of 5-FU is needed to induce the same effect.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Given that in this study we found that mut-p53 activates β-catenin/Wnt signaling, and we have recently reported that canonical Wnt activation plays an essential role in inducing chemoresistance to 5-FU in colon cancer cells (Moreno-Londoño et al. 2023 ), we investigated whether mut-p53 could participate in the induction of chemoresistance to 5-FU. We found that endogenous expression of wtp53 explains the sensitivity to low doses in the RKO cell line, contrary to mutp53, where more concentration of 5-FU is needed to induce the same effect.…”
Section: Discussionmentioning
confidence: 85%
“…We recently reported that canonical Wnt activation plays an essential role in inducing chemoresistance to 5-Fluorouracil (5-FU) in colon cancer cells (Moreno-Londoño et al. 2023 ). Given that in this study, we found that mut-p53 activates β-catenin/Wnt signaling, we then investigated whether mut-p53 could also participate in this resistance induction.…”
Section: Resultsmentioning
confidence: 99%
“…Association between stem cell molecules and their derived signals with the evolution of the tumorigenic process is widely accepted [26,27]. It has been proposed that intestinal stem cells represent an important part of the origin of CRC [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, inhibitors of the Wnt/β-catenin pathway, such as PRI-724 and LGK974, have shown promise in preclinical studies. 50 52 Monoclonal antibodies : They target CSC-specific surface markers, such as CD133 and CD44, and have been developed. For example, a monoclonal antibody against CD133 (AC133) has been shown to reduce tumor growth and metastasis in preclinical models.…”
Section: Potential Therapeutic Strategies Targeting Cancer Stem Cells...mentioning
confidence: 99%
“…For example, inhibitors of the Wnt/β-catenin pathway, such as PRI-724 and LGK974, have shown promise in preclinical studies. 50 52 …”
Section: Potential Therapeutic Strategies Targeting Cancer Stem Cells...mentioning
confidence: 99%